2005
DOI: 10.1111/j.1469-7580.2005.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in rat uterine sympathetic nerves: the role of TrkA and p75 nerve growth factor receptors

Abstract: Uterine sympathetic innervation undergoes profound remodelling in response to physiological and experimental changes in the circulating levels of sex hormones. It is not known, however, whether this plasticity results from changes in the innervating neurons, the neuritogenic properties of the target tissue or both. Using densitometric immunohistochemistry, we analysed the effects of prepubertal chronic oestrogen treatment (three subcutaneous injections of 20 µ g of β -oestradiol 17-cypionate on days 25, 27 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 71 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…It seems that E2 could also contribute to the loss of neurons in the porcine CaMG by desensitization of these cells to NGF, which has previously been observed in rat DRG neurons following a single injection [38] and long-term [22] replacement of estrogen. Also, significant reduction in the number of neurons displaying p75 protein has been observed at the end of pregnancy, when estrogen levels are increased [42]. Moreover, considering the expression of ERs by neurons in autonomic and sensory areas of the lumbosacral spinal cord that have connections with female reproductive system [43], it is possible that the reduction in the number of postganglionic neurons found in the present study may partly result from changes of the density of ERs receptors on preganglionic neurons in response to E2 treatment, which could ultimately affect both the morphology and activity of these cells and consequently disturb the neuronal network function.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that E2 could also contribute to the loss of neurons in the porcine CaMG by desensitization of these cells to NGF, which has previously been observed in rat DRG neurons following a single injection [38] and long-term [22] replacement of estrogen. Also, significant reduction in the number of neurons displaying p75 protein has been observed at the end of pregnancy, when estrogen levels are increased [42]. Moreover, considering the expression of ERs by neurons in autonomic and sensory areas of the lumbosacral spinal cord that have connections with female reproductive system [43], it is possible that the reduction in the number of postganglionic neurons found in the present study may partly result from changes of the density of ERs receptors on preganglionic neurons in response to E2 treatment, which could ultimately affect both the morphology and activity of these cells and consequently disturb the neuronal network function.…”
Section: Discussionmentioning
confidence: 99%
“…Richeri and co-workers (2005) have observed that the mean size of uterine-projecting sympathetic neurons decreases in pregnant rats. This reduction could reflect the degeneration of sympathetic fibers, or a reduction in neurotrophins or in neurotrophin receptors (Richeri et al 2005). In addition, Klukovits and co-workers (2002) have described a reduction in the number of nerves in pregnant rats by using fluorescence histochemistry.…”
Section: Reduction Of Innervation During Pregnancy and At Estrusmentioning
confidence: 98%
“…Furthermore, in addition to changes in neurotrophic factor availability, sex hormones might regulate plasticity in uterine sympathetic nerves by altering their receptivity to neurotrophins (Richeri et al 2005;Hasan et al 2005).…”
Section: Role Of Neurotrophic Factorsmentioning
confidence: 99%
“…Animals were killed by an overdose of sodium pentobarbital on the day after completion of treatment. This regimen was selected because it provoked a substantial degree of uterine sympathetic denervation and reduced the atrophic changes induced by ovariectomy in the uterus Richeri et al 2005). Vehicle-treated (peanut oil; Sigma-Aldrich, USA) OVX rats were killed 3 days following surgery.…”
Section: Animals and Treatmentsmentioning
confidence: 99%